2021
DOI: 10.1021/jacsau.1c00400
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Single-Molecule Indicator of Solvent Effects

Abstract: The study of the microscopic structure of solvents is of significant importance for deciphering the essential solvation in chemical reactions and biological processes. Yet conventional technologies, such as neutron diffraction, have an inherent averaging effect as they analyze a group of molecules. In this study, we report a method to analyze the microstructure and interaction in solvents from a single-molecule perspective. A single-molecule electrical nanocircuit is used to directly analyze the dynamic micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A key advantage of molecular electronics lies in the vast array of structural and electronic functionalities available, which vary based on the synthesis method employed. [6][7][8][9][10] The operational characteristics of molecular devices can be ne-tuned by modifying either the molecular backbone or the edge groups that connect to the electrodes, see ref. [11][12][13] for further details.…”
Section: Introductionmentioning
confidence: 99%
“…A key advantage of molecular electronics lies in the vast array of structural and electronic functionalities available, which vary based on the synthesis method employed. [6][7][8][9][10] The operational characteristics of molecular devices can be ne-tuned by modifying either the molecular backbone or the edge groups that connect to the electrodes, see ref. [11][12][13] for further details.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Schematic diagram of a single‐molecule model reaction to detect solvent effects. Reprinted with permission, [ 40 ] Copyright 2021, American Chemical Society. (c) Schematic diagram of the resistance switching via single‐molecule Fries rearrangement.…”
Section: Single‐molecule Dynamics Based On Single‐molecule Junctionsmentioning
confidence: 99%
“…For example, a single‐molecule electrical nanocircuit was used to directly detect the microscopic heterogeneity of the solution and compare interactions in solvent networks (Figure 2b). [ 40 ] Experimental results showed that RS and intermediate (IM) have opposite solvent polarity preference, with IM tending to be stable in high‐polarity solvents while RS tends to be stable in low‐polarity solvents. As solvent polarity increased, the dwell time τ (kinetics) of IM gradually increased and contributed a major proportion of the conductance states (thermodynamics).…”
Section: Single‐molecule Dynamics Based On Single‐molecule Junctionsmentioning
confidence: 99%
“…However, to further guide the macroscopic synthesis and industrial production, the gap between single molecule and ensemble should be bridged. Following the above train of thought, SMD can be regarded as the starting point to investigate the emergent complexity from bottom to top . One unique example is to measure the polymerization dynamics of one chain, demonstrating the emergent anomalous behaviors accompanied by increased molecular numbers .…”
Section: Introductionmentioning
confidence: 99%
“…Following the above train of thought, SMD can be regarded as the starting point to investigate the emergent complexity from bottom to top. 20 One unique example is to measure the polymerization dynamics of one chain, demonstrating the emergent anomalous behaviors accompanied by increased molecular numbers. 13 However, the universal method of measuring the cross-correlation among single-molecule organic reactions and especially the contained elementary step remains a nontrivial task.…”
Section: ■ Introductionmentioning
confidence: 99%